DEVELOPMENT OF LEARNING PROCESSES IN KINDERGARTEN CHILDREN - Mardonova Farangiz Ikrom qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the development of thinking and cognitive processes in children of kindergarten age. The processes of thinking and cognition begin to develop very rapidly in the kindergarten age of the child. This is due, firstly, to the relative increase in life experience in children of kindergarten age, secondly, to the fact that children’s speech is well developed during this period, and thirdly, to the fact that children of kindergarten age have a lot of free and independent actions.